UJI PEMBERIAN PUPUK KANDANG BURUNG PUYUH TERHADAP HASIL PRODUKSI SAWI HIJAU (Brassica juncea L) - Latifatul Khulud (grafting, 2021)
The purpose of this study was to determine the effect of quail manure application on the production of mustard greens. This study was conducted using a Randomized Group Design (RAK) with 5 levels and 3 repeats, with a factor of quail manure (P) 0 tons / ha (P0), 5 tons / ha (P1), 10 tons / ha (P2), 15 tons / ha (P3), 20 tons / ha (P4), 25 tons / ha (P5). The results of research on the application of quail manure to the production of mustard greens (Brassica Juncea L) have a noticeable influence on changing the length, leaf circumference, plant length, plant weight and stem diameter. The application of manure manure for quail droppings of 20 tons/ha (P4) provides the highest variable for all growth and yield of mustard plants.